Isolation and characterization of novel bioactive peptides from legume seed wastes and their application as eco-friendly coating improve the physicochemical, microbiological, aroma, and ripening properties in probiotic-enriched Ras cheese - Samir A. Mahgoub; Hayfa Habes Almutairi; Nourhan H.I. Abd-El Fattah; Ashraf S. El-Sayed; Merfat O. Aljhdli; Salah A. Khalifa; Ahmed M. Saad; Layla A. Almutairi; Mohammed A. Alqahtani; Eman A. Beyari; Wafaa Ahmed Alhazmi; Nahed A. El-Wafai; et al. (Results in Engineering)
Valorizing food waste into bioactive compounds is a growing global trend. The current study aimed to evaluate the physicochemical, functional, and bioactive properties of chickpea seed waste peptides (CWP) and pea seed waste peptides (PWP) and assess their potential in enhancing probiotic-enriched Ras cheese. The findings revealed that CWP exhibited a higher degree of hydrolysis (32% at 40 min) compared to PWP (29%). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed protein band reduction upon trypsin hydrolysis, indicating peptide formation, with lower molecular weights of CWP and PWP reaching 17 kDa and 20 kDa, respectively, after 40 min. Fourier transform infrared spectroscopy (FTIR) indicated structural changes in amide-I regions (1642 cm⁻¹ for CWP, and 1652 cm⁻¹ for PWP). The amino acid composition analysis demonstrated a superior essential amino acid profile in CWP (42.2%) compared to PWP (34.3%), although both were deficient in methionine. Functionally, CWP demonstrated superior water-holding (8.9 g/g) and oil-holding (7.2 g/g) capacities, while bioactive assays showed stronger antibacterial effects against Listeria innocua (22.45 mm) and Escherichia coli (25.35 mm) and notable anticancer activity against HePG-2 and MCF-7 cells (83–86% inhibition at 100 µg/mL, IC₅₀ 20 µg/mL for CWP compared to 25 µg/mL for PWP). In probiotic cheese development, prebiotic (CWP and PWP) encapsulation with carrageenan, locust bean gum, and gum Arabic enhanced probiotic viability (87.16% survival for Bifidobacterium animalis subsp. lactis), improved moisture retention, lowered pH, and increased proteolysis. Microbiological stability improved with reduced spoilage microorganisms and higher lactobacilli and bifidobacterial counts (8.5 log CFU/g). Sensory evaluation favored probiotic cheeses, particularly those with CWP, for flavor, texture, and overall acceptability. Principal component analysis (PCA) distinguished probiotic cheeses from controls, underscoring the benefits of encapsulation and protein hydrolysates. This study highlights the potential of CWP and PWP as functional food ingredients with antibacterial and anticancer properties. Furthermore, it demonstrates the effectiveness of encapsulating B. animalis subsp. lactis BB-12 and Lactobacillus plantarum LC484006.1 with a whey-based coating containing carrageenan, locust bean gum, gum Arabic, and bioactive peptides to enhance their survival in Ras cheese during ripening, positively impacting the cheese's physicochemical and microbiological quality.